Penerapan Unsur Tindak Pidana oleh Penyidik Terhadap Tindakan Penebangan Pohon pada Kawasan Hutan Lindung - Pratama, Yuda Amgu; Ismansyah, Ismansyah (UNES Law Review, 2023)
Reports of cases of illegal logging that occurred in areas of West Sumatra province were based on data from the Ditreskrimsus and Satwil Sejajaran Polda West Sumatra that reports of criminal acts of illegal logging at the Pasaman Police were 5 (five) cases, Dharmasraya Police were 2 (two) cases, Pesisir Selatan Police with 9 (nine) cases, Tanah Datar Police with 3 (three) cases. This study uses an empirical juridical approach. The Application of Elements of Crime by Investigators at the Tanah Datar Police Criminal Investigation Unit Against the Action of Logging Trees in Protected Forest Areas. Subjectively the element applied is "everyone" which is aimed at the person who did it. The suspect was logging trees in a forest area that was not in accordance with the forest utilization permit located in the Bukit Mantobak Forest Area in the Guguak Bancah Jor area. Galanggang Nag. Edge Selo Kec. Lintau Buo Utara Kab. Flat Land. The objective element is the act committed, namely illegal logging of trees in the forest area. While Article 55 paragraph (1) to 1e of the Criminal Code is applied because it is done jointly because there are people who order to cut down trees in the forest area without having a permit and the others are people who participate in committing a crime. Obstacles in the Application of Elements of a Criminal Act by Investigators at the Satreskrim Polres Tanah Datar for the Action of Logging Trees in Protected Forest Areas is an internal factor, namely the human factor (law enforcement officials) where the lack of technical skills related to mastery in the field of licensing in the forestry sector. External factors include the relatively low level of public legal awareness, the reluctance of members of the public to become witnesses, because they are busy and because they are threatened by suspects.